On the significance of crop‐type information for the simulation of catchment hydrology. Issue 6 (22nd April 2014) - Loosvelt, Lien; Pauwels, Valentijn R. N.; Verhoest, Niko E. C.
Abstract Spatially distributed hydrological models require information on the land cover pattern, as it directly influences the generation of run‐off. However, it is not clear which detail of land cover information is suitable for simulating the catchment hydrology. A better understanding of the relationship between the land cover detail and the hydrological processes is therefore required as it would enhance a successful application of the hydrological model. This study investigates the relevance of accurate information about the crop types in the catchment for the simulation of run‐off, baseflow and evapotranspiration. Results reveal that adding knowledge about the crop type in the model simulation is redundant when area‐averaged water flux predictions are intended. On the contrary, when a spatial distribution of water flux predictions is desired, it is meaningful to increase the land cover detail because an increased heterogeneity in the land cover map induces an increased heterogeneity in the hydrological response and locally reduces the uncertainty in the model prediction up to 50%. To assess the land cover uncertainty and to locate the regions for which the reduction in prediction uncertainty is the highest, the thematic uncertainty map (constructed through fuzzy logic) is shown to be a useful tool. Copyright © 2014 John Wiley & Sons, Ltd.